2001
DOI: 10.1159/000047372
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Rotational Atherectomy in the Treatment of Bifurcation-Type Coronary Lesions

Abstract: Background: Bifurcational coronary lesions present a major interventional challenge. The differential cutting mechanism of high-speed rotational atherectomy (HSRA) may provide a favourable technique of treating this complex lesion subtype. Methods: We evaluated the use of HSRA (32 lesions) compared to balloon angioplasty (BA) (118 lesions), with provisional stenting in both groups, in a non-randomised, retrospective study of 150 bifurcation-type lesions. Results: The HSRA/stent group had a high primary success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…SB preservation is a critical issue in the intervention of true bifurcation lesions. In the time of bare metal stent (BMS) and even in the era of early drug‐eluting stent (DES), SB RA is mainly used for debulking of large plaques, but not for heavy calcification . RA was first introduced two decades ago to treat bifurcation lesions with huge plaque burden in a “plaque debulking” manner rather than “plaque modification” for heavily calcified lesions as in the current study .…”
Section: Discussionmentioning
confidence: 88%
“…SB preservation is a critical issue in the intervention of true bifurcation lesions. In the time of bare metal stent (BMS) and even in the era of early drug‐eluting stent (DES), SB RA is mainly used for debulking of large plaques, but not for heavy calcification . RA was first introduced two decades ago to treat bifurcation lesions with huge plaque burden in a “plaque debulking” manner rather than “plaque modification” for heavily calcified lesions as in the current study .…”
Section: Discussionmentioning
confidence: 88%
“…We conducted a literature search to identify all published coronary Rotablator studies with clearly defined primary endpoints [42][43][44][45][46][47][48][49][50]. As presented in TABLE 1, the majority of the studies identified did not meet their primary endpoints.…”
Section: Rotational Atherectomymentioning
confidence: 99%
“…However, the combination of this classification with a number of wire, balloon, and atherectomy techniques accounts for all variants already reported or published [51][52][53]. We have decided to retain the initial denomination given to each individual technique, or, in the presence of several denominations, to select the most straightforward.…”
Section: Definition and Denomination Of Coronary Bifurcation Lesion Tmentioning
confidence: 99%